A quick and effective approach for removing Ni(II) from paper mill wastewater with magnesium ferrite nanoadsorbent: method development, reusability, isotherm models, and adsorption kinetics - Bahcivan, Aleyna; Atakol, Arda; Zaman, Buse Tugba; Bozyigit, Gamze Dalgic; Demir, Selami; Bakirdere, Sezgin (SPRINGER, 2025)
The removal of Ni2+ ions from the effluent of the paper mill was accomplished by using magnesium ferrite nanoparticles. The nanoparticles were produced through a sol-gel process at low temperatures. Experimental factors were meticulously optimized to enhance the adsorption process. Optimal conditions were determined to be 1.0 mL of buffer solution with a pH of 8.0, 100 mg of nano-sorbent, and mixing for 30 min. When these conditions were put to test, the removal efficiency was enhanced to >= 98.4%. Additionally, it was discovered that the nanoparticles exhibit exceptional reusability upon regeneration after the first use. The investigation of adsorption equilibrium was conducted utilizing the Langmuir, Freundlich, and Sips models. The Sips isotherm demonstrated the strongest correlation with the experimental results, as indicated by the coefficient of determination (R2) of 0.9976 while the reaction order was estimated as 1.61 by the kinetic model.
Keywords: Nickel; Magnesium ferrite; Paper mill; Wastewater; Adsorption; Isotherm; HEAVY-METALS; MGFE2O4; GASES; Chemistry; Science & Technology - Other Topics; Materials Science